Primary Multidrug-Resistant Mycobacterium Tuberculosis (P-MDRTB) in Gorgan, Iran - Mehravar 1, Fatemeh; Bazrafshan 2, Behnaz; Abbasi 3*, Abdollahe; Golsha 3, Roghieh (Shahroud Journal of Medical Sciences, 2016)
Background: Resistance to anti-tuberculosis (TB) drugs is a global problem. Previous studies showed that the prevalence of primary MDR-TB is higher and has been increasing. The purpose of this study was to determine the primary drug resistance in strains isolated from patients with smear-positive of the new cases to anti-TB drugs.Methods: In this cross-sectional study, 266 smear positive pulmonary TB Iranian patients were enrolled during the April 2011 and March 2012. Drug Susceptibility Testing (DST) of M. tuberculosis isolates to the first-line drugs, isoniazid, rifampicin, ethambutol, and streptomycin, were performed by the proportion method using conventional Lowenstein-Jensen (L-J) medium.Results: The average age was 48.4 ± 21.3 years, and 56.5 percent were male. In this study, out of 266 pulmonary TB suspects studied, susceptibility testing was performed for 189 isolates. Resistance to at least one drug was present in 11.1% (21/189) of cases. Resistance among newly diagnosed patients was most common for streptomycin, and MDR prevalence rates (resistant to ISONIAZID and RIFAMPIN) among these patients were 2.1%.Conclusions: Our finding suggests that the incidence of MDR tuberculosis in high TB burden settings stresses the need for drug susceptibility testing to be done for every patient who is culture positive for Mycobacterium tuberculosis.